KEKERASAN DALAM RUMAH-TANGGA DI KELURAHAN PANIKI DUA KECAMATAN MAPANGET KOTA MANADO - Baghi, Maria Goretty Rawi; Mokalu, Benedicta J.; Mumu, Rudy (HOLISTIK, Journal Of Social and Culture, 2017)
Marriage is for two men in entering the household in which there is duties and responsibilities and the obligations of each individual within a family, marriage institutions warrant and protect the existence of such relationship based on the law. Undergo the cheapest and the life of the party of course not run smoothly as imagined, because of many different problems to be overcome, understanding and a sense of togetherness, so it needs, to all the outstanding issues can be faced by well.Marriage are built on the principle love and compassion and would be formed harmonious families, happy and love, but the fact that many families was not harmonious, because they felt depressed and sad because of the misunderstanding, domestic violence, both the physical violence, psychological or psychiatric, sexual, emotional, and neglect family.Domestic violence itself caused by internal and external factors, especially in the openness and technological advances information often violence caused by the media information that is not filtered out negative impact on the comfort of living householdsTo save a household, needs to be done management is psychology and educational on the violence in households, good which are curative and preventive, so that would be beneficial for violent offenders in households, especially to the victims of domestic violence and its people in general.Every family want to build households a happy and of full flavor love each other whether born and inner, in other words that every family hope can build households harmonious and happy, but not all household can feel happiness because it is still there has been domestic violence.Ironically the number of violence happened better in terms of quantity or quality this indicates that there is a tendency been an increase in domestic violence in kelurahan Paniki Dua Kecamatan Mapanget Manado city.Â Keyword : violence, household, family